Gerakan Masyarakat Cerdas Menggunakan Obat Dengan Edukasi “Tanya Lima O” - Krisnawati, Monik (ABDIMAS Madani, 2023)
The availability of several pharmacies in Sendangsari Village influences the increase in community self-medication behavior. Based on Pharmacy Service Standards, pharmacists are obliged to provide drug information services to patients. GeMa CerMat, or "Ask the Five-O," is a Ministry of Health program that aims to raise awareness and change people's attitudes toward proper drug use. The "Ask the Five O's" education was held in Sendangsari Village in Pajangan. The implementation was carried out at one time, on October 15, 2022. Evaluation of the effectiveness of the activity was carried out by administering pretest and posttest questionnaires. A significant difference in knowledge between the participants before and after the guided Five-O material was obtained with a significance value of 0.00. The results of the activity show that some participants in community service activities were dominated by female participants (56%). The majority of participants had an adult age range of 13–25 years (36%). Meanwhile, high school education level (68%) and type of private job (46%) were also the main characteristics of the activity participants. The conclusion of the activity results is that most activity participants do not fully understand the "Five-O" components that must be asked when receiving drugs from pharmacists.